2019
DOI: 10.2754/avb201988040377
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selected components in seminal plasma of donkey stallions and their correlation to semen quality parameters

Abstract: Evaluation of selected components of seminal plasma as markers of ejaculate quality may be of interest when assessing the quality of semen. The aim of the study was to evaluate some biochemical parameters of seminal plasma in donkeys and compare them with the volume, concentration and motility of the ejaculate. A total of 11 ejaculates were collected from five donkey stallions (between one and three from each animal). Each ejaculate was assessed for volume, concentration and motility, and the seminal plasma bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Interestingly, to date, no studies have reported zinc and magnesium levels in the seminal plasma of Poitou jackasses. Thus, the present study reports the seminal concentrations of zinc and magnesium in this breed, where the zinc level was similar and the magnesium level was higher than those found in other domestic donkeys by Vyvial et al (37).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, to date, no studies have reported zinc and magnesium levels in the seminal plasma of Poitou jackasses. Thus, the present study reports the seminal concentrations of zinc and magnesium in this breed, where the zinc level was similar and the magnesium level was higher than those found in other domestic donkeys by Vyvial et al (37).…”
Section: Discussionsupporting
confidence: 82%
“…Also, low concentrations of glucose (0.0-0.2 mmol/L), cholesterol (0.1-0.3 mmol/L), zinc (18.1-23.7 µmol/L), and magnesium (1.6-2.8 mmol/L) were found. Zinc is a micromineral that plays an important role in many protective sperm properties, such as membrane stabilization, and antioxidant and antibacterial functions (36), and a testicular and epididymal origin has been suggested in Equidae (11,37). Magnesium is a cation related to high seminal plasma quality in boars because it improves viability by reducing sperm membrane damage (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive motility of spermatozoa (alongside semen concentration) is a good indicator of male fertility and both general state of health and health of the reproductive tract (Vyvial et al 2019). Reduced sperm motility parameters are frequently associated with inflammation and severe infection (Björndahl 2010;Vitula et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In preserved stallion semen, the exposure to BSP proteins from seminal plasma causes continuous cholesterol removal from the sperm membrane, increasing sperm sensitivity, which can render sperm extremely sensitive to cryopreservation (Calvete et al, 1994;Bergeron et al, 2004). In donkey semen, despite some reports described seminal plasma general composition (Talluri et al, 2017;Vyvial et al, 2019), there is not much available information on seminal plasma proteins. Some studies showed that seminal plasma dilution or removal from donkey semen increases sperm motility and membrane integrity after storage (Serres et al, 2002;Miró et al, 2009).…”
Section: Introductionmentioning
confidence: 99%